Intervention for improving the appropriateness of physician orders for oral medications in geriatric VIP patients during the journey to JCI accreditation - Zhu LL; Zhou Q (Dove Medical Press, 2013)
Ling-ling Zhu,1 Quan Zhou21Geriatric VIP Ward, Division of Nursing, 2Department of Pharmacy, the Second Affiliated Hospital, School of Medicine, Zhejiang University, Hangzhou, Zhejiang Province, People's Republic of ChinaWe read with great interest the study by Fadare et al,1 who assessed the prescribing pattern for elderly Nigerian outpatients and concluded that polypharmacy and the prescription of potentially inappropriate medications are major therapeutic issues in Nigeria, and there is a need for prescriber training and retraining with emphasis on the geriatric population. We completely agree with Fadare et al’s1 point of view that a low proportion of patients with potentially inappropriate medications highlights the importance of information technology in medication management. We discuss and share our perspectives in the following paragraphs.View original paper by Fadare and colleagues.